Production of activated carbons by microwave pyrolysis of industrial wastes for the removal of pharmaceuticals from water - Dias, Sandra Raquel da Silva (2018)
The presence of pharmaceuticals in water bodies, being biologically active compounds, have raised concerns due to the adverse effects in non-target organisms. With the conventional treatments, applied in the wastewater treatment plants (WWTPs), being inefficient for the removal of these contaminants, WWTPs are pointed out as the main source of pharmaceuticals into the environment. The use of adsorption, as an advanced treatment for the removal of pharmaceuticals from water, in particular by using activated carbons (ACs), has shown to be an easy-handling and cost-efficient process, without sub-products formation. Since the production of ACs can be an expensive process, due to the high energy requirements and the use of expensive precursors, the alternative microwave (MW) pyrolysis of paper mill primary sludge (PS) can be a promising solution, contributing simultaneously for industrial waste valorisation. In the scope of this work, ACs were produced by MW pyrolysis of PS impregnated in KOH (activating agent) for 10 min at 800 W, washed with hydrochloric acid and sieved to obtain the fraction of particles with a size up to 180 μm. Different ACs were obtained by changing activating agent:precursor ratios, namely 0.5:1, 1:1 and 1.5:1. The produced ACs were physico-chemically characterised. In order to assess the performance of the produced ACs, batch adsorption experiments were performed with ultra-pure water to determine the adsorption percentages of the anti-epileptic carbamazepine (CBZ). The effect of AC dosage and the effect of contact time were also tested. The obtained results have shown that, overall, the ACs produced with an activating agent:precursor ratio of 0.5:1 presented specific surface areas (SBET) between 773 and 1190 m2/g and high percentages of CBZ removed from ultra-pure water solutions, above 80 %, for AC dosages of 0.1 g/L and a contact time of 24 h. The lab-made ACs have shown a more developed porous structure than the reference commercial AC and comparable SBET. Nevertheless, under the same experimental conditions, different production batches resulted in ACs with different properties and performances, highlighting that further research work is required to optimise its production process, making it repeatable.